Nowhere to Go and Nothing to Do but Sit? Youth Screen Time and the Association With Access to Neighborhood Destinations. (January 2017) - Christian, Hayley; Zubrick, Stephen R.; Knuiman, Matthew; Nathan, Andrea; Foster, Sarah; Villanueva, Karen; Giles-Corti, Billie
With not much to do in their neighborhood, youth may spend more time in the home engaged in screen-based activities. Screen time data from 2, 790 youth in the Western Australian Health and Wellbeing Survey were linked to objectively measured count of types of neighborhood "services, " "convenience goods, " "public open space, " and "youth-related" destinations. On average, youth accrued 801 mean min/week screen time and had access to seven different types of neighborhood destinations. A larger number of different types of neighborhood "youth-related, " "service, " and "total" destinations were associated with less screen time (all p ≤ .05). A significant gender interaction was observed. Girls with access to ≥12 youth-related destinations had 109 fewer mean min/week screen time, compared with girls with 0 to 3 youth-related destinations. Providing alternatives to screen use by ensuring access to a variety of neighborhood places for structured and unstructured activities may be an important strategy for decreasing youth screen time.